2004
DOI: 10.1136/vr.155.18.547
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of palpation as a method for determining the prevalence of keel and furculum damage in laying hens

Abstract: Old breaks of the keel and furculum were identified by palpation in 500 end-of-lay hens from 10 flocks housed in free-range and barn systems, and the results were compared with the results obtained by a full dissection and inspection. The method was considered to be sufficiently precise to be used as a diagnostic tool although people using it would need to be trained. The results obtained by dissection indicated that 50 to 78 per cent of the birds in the flocks had breaks of the furculum and keel, but no other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 13 publications
7
77
2
Order By: Relevance
“…In the present study, 55Á7% of all the hens experienced a fracture, of which 84Á8% were old fractures, that is, 47% of all hens experienced a keel break during their laying period -this lies at the lower end of the range reported by Wilkins et al (2004) reflecting the slightly lower risk in cage systems. Recent keel bone fractures were nearly 5 times more common in CC hens than hens from other systems (Table 3) although this problem was particularly high in one flock of this system.…”
Section: Keel Bone Fracturesmentioning
confidence: 71%
See 1 more Smart Citation
“…In the present study, 55Á7% of all the hens experienced a fracture, of which 84Á8% were old fractures, that is, 47% of all hens experienced a keel break during their laying period -this lies at the lower end of the range reported by Wilkins et al (2004) reflecting the slightly lower risk in cage systems. Recent keel bone fractures were nearly 5 times more common in CC hens than hens from other systems (Table 3) although this problem was particularly high in one flock of this system.…”
Section: Keel Bone Fracturesmentioning
confidence: 71%
“…In previous work the prevalence of old fractures in the keel and furculum has been assessed as between 50 and 78% in non-cage systems (Wilkins et al, 2004) with no difference between barn and free-range hens, and at 60% in a study of 36 barn flocks . The type of housing system had a great effect on the prevalence of old keel bone fractures, with the value in the worst system (B) being almost twice that of the cage systems.…”
Section: Keel Bone Fracturesmentioning
confidence: 99%
“…First, palpation as a method to assess keel bone damage in laying hens is likely to miss small fractures or fractures that occur at locations of the keel that are difficult to palpate such as the lateral sites of the keel. Due to this concern, visual keel bone assessment following dissection is strongly recommended (Wilkins et al, 2004). However, in the current study, we did not palpate birds immediately before dissecting the keel bones and it is possible that small fractures or those at the dorsal and lateral sites of the keel bone were missed during the palpation assessment but found during visual inspection.…”
Section: Aviary Design and Keel Bone Damagementioning
confidence: 76%
“…As a result, the actual, true percentage of fractures may have been higher than found by palpation though we believe severe fractures were detected reliably during palpation. New fractures caused during slaughtering were associated with pooled blood near the fractured bone and were absent of callus material, an indicator of old fractures (Wilkins et al, 2004), a differentiation used to distinguish between old and new fractures. Thus, the influence of slaughtering on keel bone damage did not bias visual assessment of the keel bones and is likely not a reason for the dramatic increase at the last time point.…”
Section: Aviary Design and Keel Bone Damagementioning
confidence: 99%
“…Housing design has a substantial effect on the risk of damage, with the lowest prevalence of keel damage reported in conventional cages (17.7 %, Sherwin et al, 2010), intermediate levels of keel damage reported in furnished cages (62 %, Rodenburg et al, 2008;31.7 %, Sherwin et al, 2010;36 %, Wilkins et al, 2011), greater levels of keel damage reported in single-tier non-cage systems (50-78 %, Wilkins et al, 2004;60 %, Nicol et al, 2006;82 %, Rodenburg et al, 2008;59-67 %, Wilkins et al, 2011) and the highest level of fractures in systems with the greatest combined available heights suitable for perching (97 %, Rodenburg et al, 2008;86 %, Wilkins et al, 2011). Solving the problem of keel bone damage will require a multi-disciplinary approach, including the input of geneticists, but good perch design could play an important role in reducing the risks associated with sustained or sudden impact with solid structures.…”
Section: Description and Effects Of Perches In Different Housing Systemsmentioning
confidence: 99%